A systematic review of neglected tropical diseases (NTDs) in Myanmar. - Myo Maung Maung Swe; Aung Pyae Phyo; Ben S Cooper; Nicholas J White; Frank Smithuis; Elizabeth A Ashley (Public Library of Science (PLoS), 2023)
Background Neglected tropical diseases (NTDs) affect most impoverished communities in developing countries, like Myanmar in Southeast Asia. NTDs have been understudied and underreported in Myanmar. Methods A systematic review of published and grey literature (1900-2023) on neglected tropical diseases (NTDs) in Myanmar was conducted. The literature search included five international databases: PubMed, EMBASE, Ovid Global Health, and Web of Science Core Collection and one national database: the Myanmar Central Biomedical Library (locally published papers and grey literature). The selection criteria included articles with all types of study designs of current or previous infections conducted in humans, that reported NTDs, recognised by WHO, US CDC, and listed in PLoS NTDs. We included melioidosis and rickettsioses which we consider also meet the definition of an NTD. Results A total of 5941 records were retrieved and screened, of which, 672 (11%) met the selection criteria and were included in this review. Of the included articles, 449 (65%) were published after 2000 and 369 (55%) were from two regions (Yangon and Mandalay) of Myanmar. Of the included articles, 238 (35%) reported bacterial NTDs, 212 (32%) viral NTDs, 153 (23%) helminth NTDs, 25 (4%) protozoal NTDs and 39 (6%) reported more than one aetiology. Based on reported frequency in descending order, the bacterial NTDs were leprosy, Escherichia coli enteritis, salmonellosis, cholera, shigellosis, melioidosis, leptospirosis and rickettsioses; the viral NTDs were dengue, chikungunya and Japanese encephalitis virus (JEV) infection; the protozoal NTDs were amoebiasis, giardiasis and leishmaniasis, and the helminth NTDs were ascariasis, trichuriasis, hookworm disease, filariasis and strongyloidiasis. Conclusion This review summarises NTDs reported in Myanmar over the past 100 years. The findings suggest that most NTDs are likely to be under reported, especially from the majority of the country which is far from academic centres. Research capacity building together with strengthening of laboratory systems would lead to better understanding of the true burden of NTDs in Myanmar. Trial registration PROSPERO registration ID: CRD42018092627.